Um Percurso de Estudo e Pesquisa para abordar conceitos da Didática da Matemática em uma perspectiva Inclusiva - Antunes, Francieli Cristina Agostinetto (2022)
This research was carried out through the development and analysis of a Study and Research Pathway (SRP) within the scope of a discipline that includes the concepts of the Didactics of Mathematics, which compose the curriculum of the second year of the Licentiate in Mathematics course at Unioeste, campus of Cascavel. The planning and execution objective of the classes and the research was to identify to what extent the development of a SRP with academics of a discipline that works with the concepts of the Didactics of Mathematics, permeated by inclusive assumptions, contributes to teacher training in their performance in an inclusive classroom. Concepts related to the educational inclusion of people supported by Special Education were added to the syllabus of the discipline, more specifically, the deaf, the blind, or people with low vision. The approach of concepts related to the discipline, the Inclusion and the mathematical object chosen as a background for the work in the classroom, affine functions, was based on the paradigm of 'questioning the world', based on the Anthropological Theory of the Didactic (ATD), in an attempt to answer the research question through the analysis of the data produced. During the thirty meetings of PEP execution, twenty-two Study and Research Activities (SRA) were proposed in order to articulate 'Mathematics Didactics', 'Inclusion' and 'affine functions'. The SRP started with the elaboration of a teaching sequence, prepared by the academics, on affine functions for a class in the 1st year of High School and it was concluded with the elaboration of another teaching sequence, on the same mathematical object and for the same school level, but considering a class that has, among its students, students who are deaf, blind or with low vision. The analysis data consisted of: the teaching sequences created; the written summaries of the consulted works; audio recordings of group discussions; materials produced by students; the teacher-researcher's observations of the discussions held with the entire class; and the audio recording of the semi-structured, individual interview, recorded at the end of the SRP. The final teaching sequence configured the expected answer to the question proposed to the teachers in training at the beginning of the development of the SRP: how to elaborate a teaching sequence to promote the learning of affine functions in a class in the 1st year of High School in an inclusive school which has, among its students, students who are deaf, blind or with low vision? The SRA contributed to the construction of the final teaching sequence, which includes the proposals of classes and tasks so that students in a situation of Inclusion can perform them autonomously and, at the same time, collaborative, since it involves the other students in the class. We identified through research that it is possible to reflect on Inclusion without the theme being part of the syllabus of the discipline.